AB0826-HPR Cognitive functioning of patients with systemic lupus erythematosus with moderate activity of the disease. preliminary report. (23rd January 2014) - Mojs, E. H.; Samborski, W.; Leszczynski, P.; Pawlak-Bus, K.; Wojciak, R.; Jeka, S.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which the aetiology includes genetic and environmental factors. The autoimmune mechanisms of the disease are the potential risk factors for the impairment some brain functions also. Objectives: The goal of the study was to evaluate some cognitive functions belong to the group of executive ones in a group of patients with SLE. Executive functions are related with activity of frontal lobes of brain. The research involved a group of 64 patients with SLE, aged 19-62 yrs, the mean 41, 2 yrs, median disease duration 8, 3 yrs, the median results in SELENA/SLEDAI 11 points what suggests the moderate activity of the disease. 95% of pts were treated with chlorochine or hydroxychlorochine. Methods: To verify research hypotheses neuropsychological tests such as 10 – word list, direct memory task for sensible words, digit test, test for evaluation the attention – concentration and the ability of sustaining -D2, attention test CTT, language competencies – Fluency Test, Hand Laterality Test, and estimation of the intelligence – Raven Test. Identification and Interpretation of Emotions in Social Situations and Achenbach's CBCL were used. The research hypotheses were verified by way of Multi – Factor Analysis of Variance (Anova) for quantitative data and Kruskal – Wallis Test for ordinal data while Bonferonni – Dunn Test or Tukey's HSD were used to find relevant differences between groups. Additionally, in case of nonhomogenous variables, non – parametric tests such as Mann – Whitney Two Sample Test and Kruskal – Wallis Test for three or more samples were applied to verify the result of analysis of variance. For nominal data Chi – square test was used while Pearson r was used to measure the correlation between variables. Ethical approval for data management was obtained from the Ethics Committee of the Poznan University of Medical Sciences. Results: The results show that 14, 5% pts with SLE have neurological disorders. Cognitive impairments including direct memory, learning and attention dysfunctions were noticed in 51, 6% of all examined pts. In a group with neurological disorders almost all pts revealed low scores in CTT (below 100 sec), the median for Short term memory was 5, 6 elements, the median of D2 was below normal scores according to the age of pts. The results of 10 word test was 30, 4 what is low result in comparison to the healthy ones. Conclusions: The model of SLE treatment should include neuropsychological rehabilitation in order to improve patient's quality of life and to prevent cognitive and social impairments. Disclosure of Interest: None Declared